(3ebGdI aj GdMeGes - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf agPg ebGdI dWjaI ai GdcdGe Ydi GdMeGe hefGaYg hcjajI GSJYeGdI ddUMjM hGdeQjV ,hJOGQc GdNWC GdhGbY ai GSJYeGdg GdabgGA HETGQg TjN GdeSdejf hhGQK Ydhe GdCfHjGA hGdeSdejf s
(3BNQgG (B:s
(3hdPdc jbhi GdgVe hjUdH GdCYVGA hjcTagG , hjefY GSJYOGOgG dfahP VQQ GdghGA hGddg CYde JeJ GdebGdI HMeO Gddg hYhfg hMSf JhajbI s
(3Vef eLehY s
(3GfXQgG eY OaY GdSehe Qbe (B" 467"s
(3ai ebOeI hNeSI CHhGHs
(3CdagG HETGQI CHj GdMSf GdHcQi GdUOjbis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B245 s
Keywords: (3GdWHs